Host-Guest Complexation of Apple Antioxidant Quercetin By Linked b-Cyclodextrin Dimer - Nguyen, Hoa-Du; Pham, Duc-Truc; F. Lincoln, Stephen (Asian Journal of Chemistry, 2010)
In aqueous phosphate buffer at pH 7.0 (3.3 % ethanol, I = 0.10 mol dm-3 at 298.2 K) quercetin forms host-guest complexes with b-cyclodextrin (bCD) and N,N'-bis(6A-deoxy-6A-b- cyclodextrinyl)urea (66bCD2ur) of stoichiometry bCD.Qc and 66bCD2ur.Qc, the analogous K1 = 537 and 1901 dm3 mol-1, respectively, showing a good cooperative binding of two annuli of the dimer to the guest. The complexation of quercetin (Qc) by b-cyclodextrin (bCD) and N,N'- bis(6A-deoxy-6A-b-cyclodextrin)urea (66bCD2ur) in D2O was studied by 2D ROESY 1H NMR provided evidence for complexation of quercetin into bCD annuli. The models of complexes were constructed and energy minimized.